Model pengembangan formula kompon vulkanisir ban luar dump truck dengan filler fly ash - Nasruddin .; Sudirman .; A. Mahendra; A. Haryono (Balai Riset dan Standardisasi Industri Palembang, 2014)
Retread tire dump trucks imported and local characterization has been performed as a basis for modeling the development of a formula dump truck tire retreading. Materials used include natural rubber SIR 20, Thermoplastic Elastomer (inserting ETP), carbon black, silica and fly ash. The test results showed that the addition of the ETP on natural rubber SIR 20 for retread tire dump trucks can increase the hardness of 3.03%, 3.87% tensile strength, tear strong 15.46%, 100% modulus with a value of 36.28%, the modulus 300% with a value of 27.71% and 52.46% abrasion value. Testing of mechanical properties in fresh condition after aging (aging) and after ozone exposure given PPHM 25 for 3x24 hours at a temperature of 40°C shows, the addition of ETP a positive effect on some mechanical properties. The test results showed the addition of SEM-EDS ETP can protect natural rubber from ozone attack. Fly ash is added to the compound of formula has a tendency to bind to one another, so that the process of making the formula developed an innovative mixing with coupling agent Si type of PEG 400 and 69.Keywords: natural rubber, ETP, carbon black, fly ash, dump truck tire compound.AbstrakVulkanisir ban luar dump truck impor dan lokal telah dilakukan karakterisasi sebagai dasar untuk membuat model pengembangan formula vulkanisir ban luar dump truck. Bahan yang digunakan antara lain karet alam SIR 20, Elastomer Termoplastik (inserting ETP), carbon black, silica dan fly ash. Hasil pengujian menunjukkan, penambahan ETP pada karet alam SIR 20 untuk vulkanisir ban luar dump truck dapat meningkatkan kekerasan 3,03%, kuat tarik 3,87%, kuat sobek 15,46%, modulus 100% dengan nilai 36,28%, modulus 300% dengan nilai 27,71% dan abrasi = 52,46%. Pengujian sifat mekanik pada kondisi segar setelah proses penuaan (aging) dan setelah diberi paparan ozon 25 pphm selama 3x24 jam pada suhu 40°C menunjukan, penambahan ETP memberikan efek positif pada beberapa sifat mekanik. Hasil pengujian SEM-EDS menunjukan penambahan ETP dapat melindungi karet alam dari serangan ozon. Fly ash yang ditambahkan pada formula kompon memiliki kecenderungan berikatan satu sama lain, sehingga pada proses pembuatan formula dikembangkan suatu inovasi pencampuran dengan coupling agent jenis PEG 400 dan Si 69.Kata Kunci : karet alam, ETP, carbon black, fly ash, kompon ban luar dump truck.